A study on the box size and orientation effects on direct and interface shear tests - Gümüşalan, Suad Mert. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2021., 2021)
The large size large displacement shearing device has been under development nearly for the last decade at Bogazici University. Upper box movement, three times larger lower shear box size and pneumatic muscles sliding on rails for normal loading are the unique parts of the device. Upper box movement is essential for multipurpose use: model pile tests, inclined plane tests, residual shear strength tests. The movement of the upper box caused soil loss at large displacements, during direct shear testing, resulting of very low internal friction angles. The objective of this study was to solve this problem using different methodologies. First set of experiments resulted much lower values than those reported in the literature. Besides these low values, normal stress loss, loading platen rotation and a dilation in front of the upper shear box were observed. The second set of experiments was performed after the partitioning of the lower shear box into three equal compartments. However the obtained measurements were still inconclusive. The third set of experiments was performed by partioning the lower box with one metal platen and a wooden wedge to increase the rigidty of the system. The obtained results were consistent with the direct shear test and the values reported in the literature. The interface shear strength experiments did not show any problem. The size effect between the devices were observed. The solution of the problem related to upper box movement ensured the versatility of the testing system. The planned experimental program could not be finished due to the pandemic restrictions.
Keywords: Shear strength of soils.; Shear (Mechanics)